Pengaruh Penggunaan Rebusan Air Daun Sirih Hijau (Green Betel Leaf) Pada Wanita Usia Subur Dengan Flour Albous Di PMB Hj.Masdewati Pohan Palembang - Novi Rida Eriyani (Jurnal Ventilator, 2023)
Flour albus or vaginal discharge is a problem that often occurs in women. Efforts that can be made to reduce the occurrence of flour albus include pharmacological (drugs from doctors) and non-pharmacological. The use of natural ingredients as herbal medicine is considered safer than the use of modern medicine because the side effects of herbal medicine are relatively small if used correctly. Betel leaves can be used as a cure for flour albus because they have the power to kill germs. The content of betel leaves is usually used in cleaning soap specifically for women. Objective: to determine the effect of green betel leaf decoction in reducing vaginal discharge in women of childbearing age. Method: pre-experimental research design (one-group pre-post test design). The sampling technique used purposive sampling totaling 15 people. Data analysis used the dependent t test to see the effect before (pre test) and after (post test) using boiled green betel leaf water by washing it directly into the vaginal area. Research results: respondents experienced a decrease in the scale of vaginal discharge from itchy to non-itchy, a reduction in the level of turbidity and viscosity. increased breast milk production obtained from the pretest and posttest. The results of the dependent t test showed a Z value of -2.111 and Asymp Sig of 0.004 <0.005. The conclusion of this study states that there is an effect of betel leaf decoction on vaginal discharge in women of childbearing age